The archaeology of Greek and Roman Troy - Rose, Charles Brian 1956- (Cambridge Univ. Press, 2013)
Machine generated contents note: 1. Troy in the Bronze Age; 2. Troy during the Archaic Period; 3. The tombs of the Granicus River Valley: the Polyxena sarcophagus; 4. The tombs of the Granicus River Valley II: the child's sarcophagus; 5. The tombs of the Granicus River Valley III: the Dedetepe tumulus; 6. The tombs of the Granicus River Valley IV: the Çan sarcophagus; 7. Ilion, Athens, and Sigeion during the 5th and 4th centuries BC; 8. Ilion in the early Hellenistic period; 9. The West Sanctuary during the Hellenistic period; 10. Late Hellenistic and early imperial Ilion; 11. From the Flavians to the Byzantines; 12. The concept of Troy after antiquity